STRATEGIC ORIENTATION AND IMPACT ON THE DESIGN OF TOURISM SECURITY TECHNIQUES: AN EXPLORATORY STUDY OF THE OPINIONS OF A SAMPLE OF MANAGERS AT BAGHDAD INTERNATIONAL AIRPORT - Ihsan Adnan Abdullah; Professor Dr. Dina Hamed Jamal (Scholar Express Journals, 2023)
The current study seeks to know the impact of strategic orientation(SO) in three dimensions in design of tourist security crisis management techniques (TMDT) , IT relationship to achieving goals of Baghdad International Airport. To enhance tourism management , its crisis security with its dimensions (smart training, human resource efficiency, study sample was (70) managers , heads of departments of Civil Aviation Authority at Baghdad International Airport. The parameter was distributed on scale "Likert5" on distribution scale (70 ) a questionnaire, and (10) was retrieved (60) a valid questionnaire for statistical analysis, while (10) questionnaires were excluded for statistical analysis because of their invalidity. To report data and test hypotheses, researcher used statistical programs, including AMOS, SPSS, and V.25, in addition to a set of statistical techniques , techniques. study concluded that There is a relationship and influence of methods of strategic orientation on , design of tourism crisis management in various proportions. The study recommended the necessity of employing learning and continuous improvement of its employees by the departments and units of the civil aviation company
Keywords: Tourist Security Crisis Management Techniques; Strategic Orientation